The use of high-fidelity manikins for advanced life support training—A systematic review and meta-analysis. (August 2015) - Cheng, Adam; Lockey, Andrew; Bhanji, Farhan; Lin, Yiqun; Hunt, Elizabeth A.; Lang, Eddy
Abstract: Objectives: The objective of this study was to evaluate the effectiveness of high versus low fidelity manikins in the context of advanced life support training for improving knowledge, skill performance at course conclusion, skill performance between course conclusion and one year, skill performance at one year, skill performance in actual resuscitations, and patient outcomes. Methods: A systematic search of Pubmed, Embase and Cochrane databases was conducted through January 31, 2014. We included two-group non-randomized and randomized studies in any language comparing high versus low fidelity manikins for advanced life support training. Reviewers worked in duplicate to extract data on learners, study design, and outcomes. The GRADE (Grades of Recommendation, Assessment, Development and Evaluation) approach was used to evaluate the overall quality of evidence for each outcome. Results: 3840 papers were identified from the literature search of which 14 were included (13 randomized controlled trials; 1 non-randomized controlled trial). Meta-analysis of studies reporting skill performance at course conclusion demonstrated a moderate benefit for high fidelity manikins when compared with low fidelity manikins [Standardized Mean Difference 0.59; 95% CI 0.13–1.05]. Studies measuring skill performance at one year, skill performance between course conclusion and one year, and knowledge demonstrated no significant benefit for high fidelity manikins. Conclusion: The use of high fidelity manikins for advanced life support training is associated with moderate benefits for improving skills performance at course conclusion. Future research should define the optimal means of tailoring fidelity to enhance short and long term educational goals and clinical outcomes.